Szełomo ben Aharon - Kubicki, Sebastian (Studia Azjatystyczne, 2016)
This article aims to present the intellectual work of a prominent Karaite scholar, Solomon ben Aaron’s (of Poswol, Wilna and Troki), who was a man of great knowledge and extensive reading, including rabbinic literature. He was born in Poswol before 1665, and died in Troki in 1745 at an age exceeding 80 years. Solomon was the author of many religious writings and polemical tracts about Karaite practices and customs, such as ʾAppiryon ʿaśa lo, Migdal ʿoz, Raḵ wa-ṭoḇ, Ḥanoḵ lan-na᷾ar and Laḥem šeʿarim (known as Leḥem śeʿorim). He also wrote poems. Solomon b. Aaron was head of a Karaite Bet-Din (in Wilna), as well as a religious head of the Lithuanian Karaites. Of his private life hardly anything is known. Due to lack of data one cannot give a full picture of his life; the article thus compiles information gathered from various Hebrew texts. Alongside Karaite literature, the article employs recent findings into Karaism to verify information within the Karaite texts.